2017
DOI: 10.17116/oftalma2017133483-88
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and clinical aspects of anterior capsulotomy in femtosecond laser-assisted cataract surgery

Abstract: The review covers morphological and clinical aspects of femtosecond laser-assisted anterior capsulotomy in cataract surgery. Literature data suggests that femtosecond laser-assisted capsulotomy is more accurate in size, shape, and centration than manual. Femtosecond laser-assisted anterior capsulotomy improves the accuracy of IOL positioning within the capsular bag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Femtosecond laser, a new technology, has been applied in cataract surgery in recent years. Previous studies had reported that femtosecond laser capsulotomy improve the centration, circularity and precision of anterior capsulorrhexis (14,15). The size and shape of the anterior capsulorrhexis greatly affect surgical outcomes, including the position of the lens and the subsequent refractive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Femtosecond laser, a new technology, has been applied in cataract surgery in recent years. Previous studies had reported that femtosecond laser capsulotomy improve the centration, circularity and precision of anterior capsulorrhexis (14,15). The size and shape of the anterior capsulorrhexis greatly affect surgical outcomes, including the position of the lens and the subsequent refractive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are cases of cataracts at birth, and congenital cataracts are mostly influenced by genetic factors, which may be closely related to maternal nutrition deficiency, metabolic disorder, bacterial virus infection during pregnancy, a large amount of harmful radiation, and other factors (2,3). The main symptoms of cataracts are decreased vision, a spot-shaped fixed shadow in the visual field, one eye diplopia or polyopia, refractive changes, visual distortion, and finally color vision changes, resulting in blindness, these symptoms seriously affect the daily life of patients (4). According to reports, the incidence of cataracts is 60-70% during the period of 50-60 years old, and the incidence of cataracts over 70 years old can reach 80%.…”
Section: Introductionmentioning
confidence: 99%